Analisis perbandingan persepsi penjual dengan selera pembeli terhadap tanaman hias daun - Luqman Darmawan; Nataliningsih Nataliningsih; Nendah Siti Permana; Yayah Haeriah (Composite : Jurnal Ilmu Pertanian, 2025)
This study aims to examine sellers’ perceptions of foliage ornamental plants, identify consumer preferences, and compare the two perspectives. The research was conducted along a series of ornamental plant kiosks located on Sersan Bajuri Street, Cihideung Village, Parongpong District, Indonesia. The method used was a verificative survey. The seller population consisted of 362 individuals, from which 36 respondents were selected using simple random sampling, while 96 buyer respondents were selected using systematic random sampling. The findings indicate that sellers generally perceive ideal foliage ornamental plants as having green leaves, medium plant size, high durability, moderate popularity, small plant type, affordable price, a reasonably strategic sales location, and promotional activities primarily through social media. Conversely, buyers tend to prefer foliage ornamental plants with colorful leaves, medium size, high durability, moderate popularity, medium-sized types, affordable prices, strategic sales locations with diverse options, and social media-based promotions. Statistical analysis revealed significant differences between sellers’ perceptions and buyers’ preferences, particularly in terms of leaf color and plant type. However, an overall comparison using the Mann-Whitney U test yielded a Z-score of -1.207, with a critical Z-value of 1.96 and a significance level (2-tailed) of 0.227 (p > 0.05). These results suggest that, overall, there is no statistically significant difference between sellers’ perceptions and buyers’ preferences regarding the characteristics of foliage ornamental plants.